PENDUGAAN PARAMETER PADA MODEL LOGISTIK NOMINAL - Yunarti, Yuyun (P3M STAIN Jurai Siwo Metro, 2013)
Nominal logistic regression is an extension of binary logistic regression. Binary and nominal terms refer to how many categories are owned by the response variable Y. If Y contains only two categories the corresponding logistic regression is binary logistic regression. If the response variable Y r category covers and has a structure which takberurut (unordered) then the corresponding logistic regression is a nominal logistic regression. Of r categories owned by the response variable Y will be obtained (r -1) logit function. So that the estimate of the regression parameters paremater carried out simultaneously. Therefore the estimation is usually done by using the method of Newton-Rhapson. Keywords :Logit function, maximum likelihood estimators, method of Newton-Rhapson